Advantages and Setbacks of Industrialized Building System (IBS) Implementation: A Case Study in Sarawak - Sing Wong, Sing; Kung Lau, Ling (International Journal of Sustainable Construction Engineering and Technology, 2015)
Industrialized Building System (IBS) is an innovative technique adopted to increase the efficiency, quality and productivity of projects. However, these advantages are proven mainly for projects located in urban areas only. IBS is not a common practice for projects located in rural areas. Although there were studies about IBS in Malaysia about its advantages and setbacks, these studies were focusing on projects located in urban areas located in West Malaysia only. Hence, this paper aids to close the gap via examining advantages and setbacks of implementing IBS in rural areas of Sarawak, East Malaysia which the level urbanization is low. Qualitative method with case study approach was adopted. This paper reveals that the advantages of IBS are faster project completion, provides cleaner, neater and safer construction sites, and reduces foreign workers. However, some advantages are not applicable, i.e. high quality of work and lower total construction costs. On the other hand, this paper reveals that there is no significant difference between setbacks of IBS in rural areas of Sarawak, East Malaysia and urban areas of West Malaysia. These setbacks are resistance to change, negative perceptions of the stakeholders towards IBS designs, expensive overall construction costs, lack of knowledge and exposure to IBS technology and lack of IBS manufacturers in industry. Among these setbacks, the lack of local IBS manufacturers and expensive overall construction costs are two significant setbacks. This paper manages to provide an insight for construction firms, as well as policy maker, that are going to implement IBS in their projects in rural areas, especially in developing countries.